LncRNA MALAT1/miR‐129 axis promotes glioma tumorigenesis by targeting SOX2. Issue 8 (29th May 2018) - Xiong, Zhiyong; Wang, Luyang; Wang, Qiangping; Yuan, Ye
Abstract: We aimed to explore the interaction among lncRNA MALAT1, miR‐129 and SOX2. Besides, we would investigate the effect of MALAT1 on the proliferation of glioma stem cells and glioma tumorigenesis. Differentially expressed lncRNAs in glioma cells and glioma stem cells were screened out with microarray analysis. The targeting relationship between miR‐129 and MALAT1 or SOX2 was validated by dual‐luciferase reporter assay. The expressions of MALAT1, miR‐129 and SOX2 mRNA in both glioma non‐stem cells and glioma stem cells were examined by qRT‐PCR assay. The impact of MALAT1 and miR‐129 on glioma stem cell proliferation was observed by CCK‐8 assay, EdU assay and sphere formation assay. The protein expression of SOX2 was determined by western blot. The effects of MALAT1 and miR‐129 on glioma tumour growth were further confirmed using xenograft mouse model. The mRNA expression of MALAT1 was significantly up‐regulated in glioma stem cells compared with non‐stem cells, while miR‐129 was significantly down‐regulated in glioma stem cells. MALAT1 knockdown inhibited glioma stem cell proliferation via miR‐129 enhancement. Meanwhile, miR‐129 directly targeted at SOX2 and suppressed cell viability and proliferation of glioma stem cells by suppressing SOX2 expression. The down‐regulation of MALAT1 and miR‐129 overexpression both suppressed glioma tumour growth via SOX2 expression promotion in vivo. MALAT1 enhanced glioma stem cell viability and proliferation abilities and promoted glioma tumorigenesis through suppressing miR‐129 and facilitating SOX2 expressions.